Evaluating open access journals using Semantic Web technologies and scorecards. (February 2017) - Hallo, Maria; Luján-Mora, Sergio; Maté, Alejandro
This paper describes a process to develop and publish a scorecard from an OAJ (Open Access Journal) on the Semantic Web using Linked Data technologies in such a way that it can be linked to related datasets. Furthermore, methodological guidelines are presented with activities related to each step of the process. The proposed process was applied to a university OAJ, including the definition of the KPIs (Key Performance Indicators) linked to the institutional strategies, the extraction, cleaning and loading of data from the data sources into a data mart, the transformation of data into RDF (Resource Description Framework), and the publication of data by means of a SPARQL endpoint using the Virtuoso software. Additionally, the RDF data cube vocabulary has been used to publish the multidimensional data on the Web. The visualization was made using CubeViz, a faceted browser to present the KPIs in interactive charts.